Android studio : new media fundamentals - Jackson, Wallace (Apress, 2015)
Android Studio Content Production Fundamentals title introducing the reader to the concepts and terminology behind digital imaging (raster/bitmap/GIMP), digital illustration (vector/SVG/Inkscape), and digital audio (editing/effects/Audacity) and covers how to develop and optimize these types of content for use in Android OS using Android Studio 5.3.1. What You Will Learn? What are the primary genres of new media content production? What new media assets Android Studio supports? What are the concepts behind new media content production? How to Install and use GIMP, Inkscape, and Audacity software? How to integrate that software with Android Studio, fast becoming the most popular IDE for Android apps design and development.